2019
DOI: 10.18632/aging.102040
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive compensatory mechanisms in normal aging: a study on verbal fluency and the contribution of other cognitive functions

Abstract: Verbal fluency has been widely studied in cognitive aging. However, compensatory mechanisms that maintain its optimal performance with increasing age are not completely understood. Using cross-sectional data, we investigated differentiation and dedifferentiation processes in verbal fluency across the lifespan by analyzing the association between verbal fluency and numerous cognitive measures within four age groups (N=446): early middle-age (32-45 years), late middle-age (46-58 years), early elderly (59-71 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 67 publications
2
45
0
1
Order By: Relevance
“…A total of 225 individuals were selected from the GENIC cohort [35], a community-based study from the Canary Islands (Spain). Inclusion criteria for the current study were in accord with the basic SCD criteria published by the SCD initiative (SCD-I) working group [4]: (1) Normal cognitive performance in comprehensive neuropsychological assessment using pertinent clinical normative data (i.e., individuals did not ful ll cognitive criteria for mild cognitive impairment or dementia); (2) preserved activities of daily living and global cognition, operationalized as a Blessed Rating Dementia Scale (BRDS) [36] score ≤ 4, a Functional Activity Questionnaire (FAQ) [37] score ≤ 5, and a Mini-Mental State Examination (MMSE) [38] score ≥ 24; (3) No abnormal ndings such as stroke, tumors, hippocampal sclerosis, etc., in MRI according to an experienced neuroradiologist; (4) no medical history of neurological or psychiatric disorders (including a diagnosis of major depression), systemic diseases or head trauma; and (5) no history of substance abuse.…”
Section: Participantsmentioning
confidence: 99%
“…A total of 225 individuals were selected from the GENIC cohort [35], a community-based study from the Canary Islands (Spain). Inclusion criteria for the current study were in accord with the basic SCD criteria published by the SCD initiative (SCD-I) working group [4]: (1) Normal cognitive performance in comprehensive neuropsychological assessment using pertinent clinical normative data (i.e., individuals did not ful ll cognitive criteria for mild cognitive impairment or dementia); (2) preserved activities of daily living and global cognition, operationalized as a Blessed Rating Dementia Scale (BRDS) [36] score ≤ 4, a Functional Activity Questionnaire (FAQ) [37] score ≤ 5, and a Mini-Mental State Examination (MMSE) [38] score ≥ 24; (3) No abnormal ndings such as stroke, tumors, hippocampal sclerosis, etc., in MRI according to an experienced neuroradiologist; (4) no medical history of neurological or psychiatric disorders (including a diagnosis of major depression), systemic diseases or head trauma; and (5) no history of substance abuse.…”
Section: Participantsmentioning
confidence: 99%
“…In our previous study, we showed that the contribution of cognitive functions to verbal fluency differed across age groups, and we suggested that this could be due to compensatory processes [ 9 ]. In the current study, we confirm that hypothesis and show that high CR and efficiency levels could be at the base of compensatory mechanisms to maintain performance in phonemic fluency with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Compensation refers to the maintenance or enhancement of performance by recruiting brain areas or networks not normally used for a specific task, as a response to brain deterioration [ 7 ] or high cognitive demands [ 8 ]. From a cognitive perspective, compensation can be approached by investigating how different cognitive functions are associated with or contribute to language abilities [ 9 ]. In particular, performance in phonemic fluency has been associated with processing speed [ 10 12 ], attention [ 13 , 14 ], lexical access [ 15 ], executive functions [ 14 , 16 19 ], and memory [ 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linguistic tasks including accuracy and speed of confrontational picture naming (Tsang and Lee 2003) and those mediated by cognitive processes, such as verbal fluency (Gonzalez‐Burgos et al . 2019), have also been shown to be vulnerable to age. Further, non‐uniform differences in some aspects of discourse production of older adults have been demonstrated with age (Sherratt and Bryan 2019).…”
Section: Introductionmentioning
confidence: 99%